The Obama education blueprint : researchers examine the evidence - Mathis, William J.; Welner, Kevin Grant (NEPC series., 2010)
In March 2010, the Obama administration released A Blueprint for Reform, setting forth its proposed revisions of the Elementary and Secondary Education Act. If enacted, the Blueprint will shape the curriculum, standards, assessments, and accountability systems of schools throughout the nation. It will also determine how and where federal education funds will be targeted, further increase federal control over K-12 education, and increase the private-sector role in the operation of public schools.In advancing this agenda, President Obama and education secretary Arne Duncan have maintained that their Blueprint recommendations are grounded in research, and in May the U.S. Department of Education issued a set of six documents presented as summaries of the research supporting their plan.As an extension of the ongoing Think Tank Review Project, the staff and Fellows of the National Education Policy Center examine these research summaries and assess how well they represent the full body of knowledge in each of the reform areas. In The Obama Education Blueprint, prominent education policy experts from across the nation offer a comprehensive analysis of the research support for the U.S. Department of Education's plan for the reauthorization of the Elementary and Secondary Education Act.This volume is designed to provide policymakers, the media, and interested citizens with what the research actually says about the administration's proposals.